Benefit of mechanical thrombectomy in acute ischemic stroke related to calcified cerebral embolus - Grand, Téodor; Dargazanli, Cyril; Papagiannaki, Chrysanthi; Bruggeman, Agnetha; Maurer, Christoph; Gascou, Gregory; Fauche, Cédric; Bourcier, Romain; Tessier, Guillaume; Blanc, Raphaël; Machaa, Malek Ben; Marnat, Gaultier; et al. (Journal of neuroradiology, 2022)
purpose - Mechanical thrombectomies (MT) in patients with large vessel occlusion (LVO) related to calcified cerebral embolus (CCE) have been reported, through small case series, being associated with low reperfusion rate and worse outcome, compared to regular MT. The purpose of the MASC (Mechanical Thrombectomy in Acute Ischemic Stroke Related to Calcified Cerebral Embolus) study was to evaluate the incidence of CCEs treated by MT and the effectiveness of MT in this indication. - Methods - The MASC study is a retrospective multicentric (n = 37) national study gathering the cases of adult patients who underwent MT for acute ischemic stroke with LVO related to a CCE in France from January 2015 to November 2019. Reperfusion rate (mTICI ≥ 2B), complication rate and 90-day mRS were systematically collected. We then conducted a systematic review by searching for articles in PubMed, Cochrane Library, Embase and Google Scholar from January 2015 to March 2020. A meta-analysis was performed to estimate clinical outcome at 90 days, reperfusion rate and complications. - Results - We gathered data from 35 patients. Reperfusion was obtained in 57% of the cases. Good clinical outcome was observed in 28% of the patients. The meta-analysis retrieved 136 patients. Reperfusion and good clinical outcome were obtained in 50% and 29% of the cases, respectively. - Conclusion - The MASC study found worse angiographic and clinical outcomes compared to regular thrombectomies. Individual patient-based meta-analysis including the MASC findings shows a 50% reperfusion rate and a 29% of good clinical outcome.
Gesehen am 31.08.2022